Analisis Pengaruh Kualitas SDM Terhadap Peningkatan Daya Saing UMKM - Lestari, Ayu; Fitria, Ida Jalilah (STIM-LPI Makassar, 2024)
This research aims to explore the influence of the quality of human resources (HR) on the competitiveness of MSMEs, with a focus on street vendors in the Lembang Square area. The research method used is qualitative, with a descriptive approach, data is collected through interviews, observation and documentation, and analyzed descriptively. The research results show that the quality of human resources (HR) in the Lembang Square area tends to be low, which affects the competitiveness of traders' businesses. Factors that influence the quality of HR (Human Resources) include education, training and experience. Traders at higher levels tend to have broader knowledge of business management, while MSME training has a positive impact on traders' understanding and business skills. However, some traders are less interested in taking part in training because of the perception that the training does not provide significant changes. Previous experience also plays an important role in developing the quality of HR (Human Resources).